Prevalence study of filariasis in two field assistant areas in medical officer of health area Kelaniya - Jasinghe, A (My University, 1993)
A study of prevalence of filariasis in two field assistant areas namely, Kelaniya and Gangaboda,in the MOH area Kelaniya was conducted during November 1993.As attempt was made to compare the prevalence of filariasis in two FA areas and knowledge, attitudes and practice of people towards filariasis in two areas were also assessed. The past Mf rates of the FA area Kelaniya and UC area Peliyagoda were analyzed. The overall Mf rate for the study population was 2.27 per cent. The Mf rates obtained for the FA areas Kelaniya and Gangaboda were respectively 3.07 per cent and 1.4 per cent. The overall clinical disease rate for the study population found to be 2.3 per cent. The corresponding figures for the FA areas Kelaniya and Gangaboda were respectively 2.5 per cent and 1.6 per cent. The study found that the prevalence of filariasis of the FA area Kelaniya to be higher than that of the FA area Gangaboda. Further the analysis of past Mf rates showed that the prevalence of infection had been higher in FA area Kelaniya during past few decades compares to the FA area Peliyagoda, but this relationship has been reversed during recent years. A distinct relationship was found between age, gender and microfilaraemia. The Mf rates, both in males and females, tend to increase up to the age of about 20 years and then remain approximately at a plateau. The most prevalent clinical forms in males and females were respectively hydrocele and lymphoedema. The mostly affected site of the lesion in males was the scrotum, and in females it was lower limbs. The chronic clinical disease found to be increasing with the age. The level of knowledge and practice found to be unsatisfactory in both areas.